Design and analysis of rocket nozzle. (2021) - Harikrishnan, R.; Lokavarapu, Bhaskara Rao
Abstract: This paper is about the design and analysis of two different rocket nozzle configurations. First configuration is without any fillets and curved surfaces and second configuration is with fillets and curved surfaces. Second configuration is used since stress concentration will be more at the corners if we don't have an optimized geometry having suitable fillets at appropriate places. Radiuses of fillets are chosen by previous studies conducted by academicians and design scientists for optimized configurations which give less overall induced stress values and hence more life. Initial configuration and Optimized configuration were drawn in ANSYS Mechanical APDL 14.5 and coupled element Quad 8 node 223 was selected for analysis. Material selected was Ti6Al4V (Grade 5). Quadrilateral mapped meshing was done and suitable boundary conditions were applied with the help of AXIMER 1.0 software. Different plots were obtained for Degrees of Freedom solution, Stress, Thermal Flux, Thermal Gradient and Total Thermal and Mechanical Strains for the two configurations. The degrees of freedom solution is calculated for all active degrees of freedom in the model, which are determined by the union of all degrees of freedom labels associated with all the active element types. It can be controlled and in this case, it would give the total number of degrees of freedom in every element of the model. Compared the two configurations and explained why the second configuration is better than the first.